Slip conditions of floor surface finish in selected public places in Kumasi, Ghana. Issue 1 (31st December 2022) - Fiagbe, Yesuenyeagbe A. K.; Ahadzie, Divine K.
Abstract: Data from the Accident Centre of the Korle-Bu Teaching Hospital, Accra, Ghana, indicate that between January 2016 and December 2017, there were 19.7% injuries due to falls with 13.7% resulting in deaths. These injuries and deaths may be due to floor surface finishes that have the tendency to cause slip fall and also exacerbated by the floor condition and footwear in contact. In this exploratory studies, tests are conducted on six selected floor surfaces and five footwear soles under dry, wed and dust or oil contaminated conditions for their slip potentials. The tests were performed with pendulum test apparatus. The footwear sole material surfaces that show better performance are leather, commando and rubber. They have Pendulum Test Value (PTV) of about 30, indicating moderate risk in slip fall and 1 in 20, 000 probability of fall. Dust contamination as applied to other floor surfaces show commando sole performing above 35 PTV with all floor surfaces. Porcelain tiles, when wet, are able to maintain above low slip potential with leather, commando and rubber camp soles but with high slip probability with others. Also, Porcelain tiles have high slip probability when contaminated with dust. From the findings, it is clear that slip fall can occur if the foot wear is not appropriate with the surface conditions. In developing countries, selecting the appropriate slip-resistant footwear is severely challenged, because of non-existent of data. Further investigation is needed for various footwear soles available leading to developing database for public education in avoiding slip falls.